Diagnostic needle arthroscopy of the scapulohumeral joint in standing sedated horses. Issue 1 (19th October 2020) - Pouyet, Morgane; Bonilla, Alvaro G.
Abstract: Objective: To describe the technique to perform diagnostic standing scapulohumeral joint needle arthroscopy with a 1.2‐mm‐diameter arthroscope in horses. Study design: Experimental study. Animals: Eight thoracic limbs in phase 1 and six horses in phase 2. Methods: In phase 1, the feasibility of the technique was evaluated by using a craniolateral arthroscopic approach. An evaluation of the visible structures of the scapulohumeral joint was performed with both a needle arthroscope and a 4‐mm‐diameter arthroscope. In phase 2, the technique was performed in six healthy sedated horses to validate the technique in live animals and to report any complications or limitations. Results: In phase 1, joint evaluation was similar between arthroscopes and allowed complete evaluation of approximately the lateral half of the humeral head and the lateral glenoid rim. In phase 2, all joints were successfully accessed, and fluid extravasation was mild. Arthroscopic visualization was complete for the centrolateral aspect of the joint in all horses and either complete (3/6) or partial (3/6) for the craniolateral and caudolateral structures, respectively. The procedure was rapidly performed and well tolerated, and no postoperative complications occurred. Conclusion: The described technique was simple and allowed direct inspection of the scapulohumeral joint. Nonetheless, the standing nature of the technique prevents evaluation of the medial aspect of the humeral head and most of the glenoid cavity. Clinical significance: Needle arthroscopy of the scapulohumeral joint is feasible in horses and offers a diagnostic technique that may improve the surgeon's diagnostic ability for certain shoulder pathologies.